2006
DOI: 10.2337/diabetes.55.04.06.db05-1434
|View full text |Cite
|
Sign up to set email alerts
|

Survival Benefits of Intensive Insulin Therapy in Critical Illness

Abstract: Tight blood glucose control with insulin reduces morbidity and mortality of critically ill patients. However, the relative impact of maintaining normoglycemia and of glycemiaindependent actions of insulin remains unknown. We therefore independently manipulated blood glucose and plasma insulin levels in burn-injured, parentally fed rabbits over 7 days to obtain four study groups: two normoglycemic groups with either normal or elevated insulin levels and two hyperglycemic groups with either normal or elevated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
121
0
14

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(138 citation statements)
references
References 49 publications
3
121
0
14
Order By: Relevance
“…However, very recently, Ellger et al (26) demonstrated in an animal model that the reduction of glucose toxicity, more than the action of insulin, improves endothelial function.…”
Section: Ceriello and Associatesmentioning
confidence: 99%
“…However, very recently, Ellger et al (26) demonstrated in an animal model that the reduction of glucose toxicity, more than the action of insulin, improves endothelial function.…”
Section: Ceriello and Associatesmentioning
confidence: 99%
“…A laboratory study manipulating insulin and glucose independently showed that the observed benefits of intensive insulin therapy required maintenance of normoglycemia. 15 Both studies in this issue of Journal of Perinatology 4,5 found a strong association between hyperglycemia and low gestational age, whereas the association between hyperglycemia and low birth weight was either less strong 4 or not significant. 5 Kao et al 4 found a significant association between their primary outcome variable, that is, a composite outcome of either mortality or late-onset culture-proven infection (odds ratio (OR) 5.07, 95% confidence interval (CI) 1.06 to 24.3) and early (the first 3 days) severe hyperglycemia (defined as mean morning glucose equal to or greater than 180 mg/dl) after adjusting for gestational age.…”
mentioning
confidence: 93%
“…Plusieurs auteurs ont proposé qu'un maintien strict de la normoglycémie était en soi responsable de ces bienfaits impressionnants, et non pas l'administration d'insuline. 7,8 En 2006, le même groupe a utilisé une stratégie semblable de contrôle strict de la glycémie chez des patients médicaux de l'USI mais n'a pas pu démontrer d'effet sur la mortalité intra-hospitalière. Un taux plus élevé d'épisodes d'hypoglycémie grave (glucose \ 2,2 mmolÁL -1 ) pourrait avoir contrecarré les bienfaits potentiels d'un contrôle strict de la glycémie au niveau de la survie chez cette population de patients.…”
Section: é Tudes Cliniquesunclassified
“…Several authors proposed that strict maintenance of normoglycemia per se was responsible for these impressive benefits, not the administration of insulin. 7,8 In 2006, the same group applied a similar strict glucose control strategy to medical ICU patients but failed to demonstrate any effect on in-hospital mortality. A higher rate of severe hypoglycemic episodes (glucose \ 2.2 mmolÁL -1 ) may have offset the potential survival benefits of strict glucose control in this patient population.…”
Section: Clinical Trialsmentioning
confidence: 99%